Optimization of the Optimum Condition of Mushroom Light Excitation (Neonothopanus sp) Bioluminescence - Qurniawati, Mila; Wulan, Ratna (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
On the South Coast of West Sumatra was found a luminous mushroom, the Neonothopanus sp. The light-emitting characteristics of this mushroom are not yet known. For the use of this bioluminescence in various fields, information on the optimal light emission conditions of the mushroom is required. This study aims to determine the optimal conditions of light emission from mushrooms such as temperature and pH. In this study, the measurement of the light spectrum of mushrooms with variations in temperature and temperature was carried out. The measuring instrument used is a nano photometer. The results showed that the maximum intensity occurred at a wavelength of 505 nm in the green area. The maximum intensity occurs at a temperature of 15 oC and pH 8.